My Flowing Life [我如水漂泊的一生]: The Songs of the Miao Cleaning Women in the Demon City [魔都] Shanghai - [熊曼谕], Xiong Manyu (Asian-European Music Research Journal, 2020)
This review is about the event “My flowing Life: the Songs of the Miao cleaning women in the Demon City Shanghai”, which took place on the afternoon of 29th December 2019, at the ceremonial hall of the Shanghai Aurora Museum. The event was designated as a workshop for practical reasons and is a “heart and sound” interaction among specific urban groups. Miao cleaners, students, scholars and the public interacting in the Demon city. The term Demon city comes from a novel written by Muramatso (1924?). It describes the city character of Shanghai in the beginning of the 20th century and reminds of long-term views of people coming from outside into the city. The cleaners came into town with their cultural habits and expectations long after that time. The event reviewed was to provide an opportunity to express these habits.